Financial Performance Assessment of PT Kimia Farma Tbk in Comparison with Other Local and Regional Companies - Dewi, Giovanni Permata; Sukarno, Subiakto (Journal of Business and Management, 2015)
abstract. In recent years, Indonesia has facing with the increase in population size alongside with the increase in people’s life expectation as one of the effect of people’s awareness in healthy life. Pharmaceutical industry in Indonesia is said to be having a positive growth with this condition therefore PT Kimia Farma Tbk, as the first pharmaceutical company in Indonesia does have an increase for its sales but unexpectedly it has a decrease for its net profit margin in 2013. Financial performance assessment will be done in order to know the real condition of PT Kimia Farma Tbk’s financial condition and it will also be compared with local and regional companies so that the result becomes clearer. The analysis method includes financial ratios analysis, DuPont analysis, BUMN framework, and Moody’s framework. The result of the assessment in 2010 - 2014 shows that PT Kimia Farma Tbk has a good financial condition but it still need to be improved with some suggestions based on the financial assessment. Keywords: Kimia Farma, pharmaceutical company, financial performance, analysis